Fetal and neonatal brain lesions following laser ablation for twin‐to‐twin‐transfusion‐syndrome as detected by pre‐ and post‐natal brain imaging. (27th October 2021) - Hochberg, Alyssa; Silber, Ronit; Avnet, Hagai; Rosen, Hadar; Katorza, Eldad; Hoffmann, Chen; Mazkereth, Ram; Lipitz, Shlomo; Weisz, Boaz; Yinon, Yoav
Abstract: Objective: To determine the rate of and risk factors for fetal and neonatal brain lesions following laser ablation for twin‐to‐twin transfusion syndrome (TTTS). Methods: A retrospective cohort study of 83 women with monochorionic twin pregnancies who underwent ablation for TTTS at a single tertiary hospital. Post‐laser survivors were followed‐up with fetal neurosonogram every 2 weeks and fetal brain MRI at 28–32 weeks of gestation; post‐natal brain imaging included neurosonogram. Cases with pre‐ and post‐natal brain lesions were compared to those without. Results: 153 fetuses survived the immediate post‐laser period and underwent brain imaging. Of these, 17 (11.11%) exhibited brain lesions on prenatal imaging studies, and 36 (32.4%) on post‐natal ultrasound. Later gestational age (GA) at the time of ablation (23.0 vs. 21.4 weeks, p = 0.0244), post‐laser twin‐anemia‐polycythemia‐sequence (TAPS) (29.41% vs. 9.56%, p = 0.035) and birthweight discordancy (30% vs. 9%, p = 0.0025) were associated with prenatal brain lesions. Earlier GA at delivery (31.0 weeks vs. 32.2, p = 0.0002) and post‐laser TAPS (25% vs. 9.33%, p = 0.038) were associated with post‐natal brain lesions. Conclusions: Survivors of ablation for TTTS are at risk for brain lesions, which can be detected prenatally. Incorporation of neurosonogram and fetal brain MRI into the routine surveillance of such pregnancies should be considered. Key points: What's already known about this topic? Laser treatment for twin‐to‐twin‐transfusion syndrome (TTTS) is associated with neurodevelopmental impairment among survivors ranging from 3% to 11% What does this study add? We demonstrated that survivors of laser ablation for TTTS are at risk for brain lesions, as detected by fetal brain ultrasound and/or MRI. Later gestational age (GA) at ablation, post‐laser TAPS and birthweight discordancy were associated with prenatal brain lesions, and earlier GA at delivery and post‐laser TAPS with post‐natal brain lesions